Growth and yield performance of different generations of seed potato as affected by PVY and PLRV (Bangladesh Journal of Agricultural Research, 2010)
Performance of potato seed tubers of first, second, third, fourth, and fifth generations were evaluated against PVY and PLRV. Potato plants grown from first generation seed tubers were free from PVY infection. Incidence of the virus was the minimal at second generation, which increased afterwards steadily by third, fourth, and fifth generations. Incidence of PLRV was minimal at first generation. It increased gradually with the advancement of generation seed tubers showing the highest incidence at fifth generation. The highest plant growth and tuber yield were recorded at second generation, which was followed by third, fourth, and fifth generations. The highest reduction in plant height, tuber number, and tuber yield were recorded in 5th generation due to infection of PVY and PLRV. Keywords: Generation evaluation; PVY; PLRV; growth; yield; potato DOI: 10.3329/bjar.v35i1.5865Bangladesh J. Agril. Res. 35(1) : 37-50, March 2010